Nurse Navigator: development of a program for Brazil - Fernanda Felipe Pautasso; Thafarel Camargo Lobo; Cecília Dias Flores; Rita Catalina Aquino Caregnato
Objective: to develop a Navigation Program for cancer patients, based on the model proposed by The GW Cancer Institute at George Washington University, adapted to the reality of a Brazilian High Complexity Center in Oncology. Method: a convergent care research applied in the development of a patient navigation care process, based on the model proposed by George Washington University, adapted for a High Complexity Center in Oncology in Brazil. Phases of the Convergent Assistance Research: conception, instrumentation, scrutiny, analysis and interpretation. These were correlated with the stages of the Program Development Cycle. Scale designed to categorize patients into navigation levels, validated by the Delphi Technique, with 12 specialists. Results: in the diagnosis, patients with head and neck cancer were defined for inclusion in the Navigation Program. Planning and implementation took place simultaneously, allowing the basic formatting of the program and its processes to be designed. Navigation Needs Assessment Scale designed to select the patient to join the Program and determine the recommended support. The scale validation had a consensus index of 96.42%. Evaluation of the stages of the cycle occurred through the adapted Plan/Do/Check/Act cycle. Conclusion: a Navigation Program was developed adapted to the Brazilian reality, and attributions of the navigators were created.